Mental Health Issues in Pregnancy and Childbirth: A Review of the Nepalese Nursing Curricula - Simkhada, Bibha; van Teijlingen, Edwin; Ireland, Jillian; Simkhada, Padam (Journal of Manmohan Memorial Institute of Health Sciences, 2021)
Background: Mental health is a difficult public health topic to talk about making it hard for frontline health workers especially countries like in Nepal. General Nurses are providing maternal and mental health care due to lack of midwives and specialist mental health nurses. Aim: This is the first study of this kind to review curricula on mental health components of pre-registration nursing training in Nepal. Methods: We conducted a rapid review of the nursing curricula on mental health and maternity care issues in Nepal. We reviewed 10 Nursing curricula of different levels of nursing. Content analysis tool was used to extract mental health related words or concepts to analyze the nursing curriculum. Findings: There is basic material included on both mental health and maternity care but nothing or little on the combination of the two topics. There appears to be a need for more communication skill, teaching and counseling at all levels of nursing. The nursing training need to focus on competency based and evidence based practice as successful strategies for perinatal mental health care. There is a great need for a curriculum to facilitate relevant training in Nepal.